2019
DOI: 10.1111/cen3.12529
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study on the effects of cognitive behavioral therapy on depression among Japanese patients with multiple sclerosis

Abstract: Objective We investigated whether cognitive behavioral therapy (CBT) improves the measures of depression and quality of life for Japanese patients with multiple sclerosis. Methods Seven patients with multiple sclerosis received an eight-session course of CBT. The session length was 60 min. The effects of CBT were assessed using the Center for Epidemiologic Studies Depression Scale for depression, and the Functional Assessment of Multiple Sclerosis for quality of life. These instruments were administered pre-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Kiropoulos et al 116 and Chruzander et al 117 found improvement in QoL at post-treatment and follow-up assessments. Kikuchi et al 118 also found a post-treatment improvement, but not significant.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Kiropoulos et al 116 and Chruzander et al 117 found improvement in QoL at post-treatment and follow-up assessments. Kikuchi et al 118 also found a post-treatment improvement, but not significant.…”
Section: Resultsmentioning
confidence: 90%
“…Interventions by Calandri et al 114 Three studies [116][117][118] focused intervention on depressive symptoms. Kiropoulos et al 116…”
Section: Demographic Factorsmentioning
confidence: 99%
“…In this context, QoL assessment provides useful information concerning the progression of the disease or the impact of therapy [ 199 , 200 ]. Various rehabilitation interventions have been evaluated using QoL, mostly in the areas of cognitive rehabilitation, psychotherapy, and the treatment of fatigue [ 201 , 202 , 203 , 204 ], all of which have shown success in improving QoL scores. Furthermore, other studies that focused on improving social support also enhanced the QoL [ 205 , 206 ].…”
Section: Subjective and Objective Measures Of Improvement After Neuro...mentioning
confidence: 99%